Avaliação da pré-carga e torque de remoção de 2 tipos de parafusos para fixação de pilares protéticos associando extensometria e ciclagem mecânica - Stüker, Rafael Augusto (2016)
The loosening and/or fracture of abutment screws is a common complication in implant-supported restorations. The torque generates a force of compression between the abutment and implant called preload, which increases when the friction between the surfaces decreases. With this objective, coating materials were developed that work as a dry lubricant. The present study compared titanium screws with titanium screws with a DLC (Diamond- Like Carbon) coating by measuring the preload and removal torque when submitted to mechanical cycling. The correlation between methods was also evaluated. For this study, 32 implants with external hexagon and 16 screws of each material were used. A cell was developed that enabled monitoring the compression between the abutment and implant with strain gauges during the cycling period. With a significance level of 5%, significant differences were observed between the groups, with the highest preload values (336.06±101.54N) being related to the lowest removal torque (24.03±2.51Ncm) in the titanium with coating group, while the titanium screws had a preload average of 269.98±91.93N and 26.41±2.94Ncm for the removal torque. We did not observe significant differences regarding loss of preload between cycling periods in both groups. DLC coated titanium screws group presented the highest preload (293.74±94.32N; 219.68±85.16N), with significant differences, and removal torque (19.82±3.47Ncm; 17.93±3.59Ncm) values after cycling, although with no significant differences. The correlation between removal torque and preload was weak for both groups, demonstrating that they evaluate different characteristics.